Effects of Berberine on Leukemia with a Focus on Its Molecular Targets - Mazandaranian, Mohammad R.; Dana, Parisa Maleki; Asemi, Zatollah; Hallajzadeh, Jamal; Mansournia, Mohammad Ali; Yousefi, Bahman (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Leukemia is common among both women and men worldwide. Besides the fact that finding new treatment methods may enhance the life quality of patients, there are several problems that we face today in treating leukemia patients, such as drugs’ side effects and acquired resistance to chemotherapeutic drugs. Berberine is a bioactive alkaloid found in herbal plants (e.g., Rhizoma coptidis and Cortex phellodendri) and exerts several beneficial functions, including anti-tumor activities. Furthermore, berberine exerts antiproliferative and anti-inflammatory effects. Up to now, some studies have investigated the roles of berberine in different types of leukemia, including acute myeloid leukemia and chronic lymphocytic leukemia. In this review, a detailed description of the roles of berberine in leukemia is provided. We discuss how berberine involves different molecular targets (e.g., interleukins and cyclins) and signaling pathways (e.g., mTOR and PI3K) to exert its anti-tumor functions and how berberine is effective in leukemia treatment when combined with other therapeutic drugs.
Keywords: inflammation